Rendőrök, akik legalizálnák a drogokat - Balázs, Dénes (Hungary : TASZ ; Lonely Films, 2007)
A short film centered on interviews with activists about legalizing and regularizing drug acquisition and consumption. Two of the reform activists served as law enforcement officials.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films